Survey data of COVID-19 vaccine side effects among Qassim University members - Alharbi, Ahmad A.; Alkhdairi, Ahmad A.; Aldubayyan, Saleh F.; Alrubaish, Nawaf S.; Alshaya, Ali K.; Alghofaily, Feras K.; Alharbi, Thamer K.; Aljemeeli, Feras A. (International Journal of Advances in Medicine, 2022)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was initially reported as a culprit for many unexplained cases of pneumonia in Wuhan, China. Since then, COVID-19 vaccine is highly recommended as a protective measure of this pandemic. This study aimed to measure the safety profile of the COVID-19 vaccine among Qassim University members. Methods: This is a cross-sectional observational study conducted among Qassim University members, Saudi Arabia. A pre-specified questionnaire was distributed among prospective members of the campus using an online survey. Participants who were vaccinated by either one or two doses were the subjects of this study. Consent was sought from the participants or next of kin and the data collection were lasted for over three months. Results: The 604 respondents were able to recruit (51.7% males versus 48.3% females). 55.6% of respondents were in the younger age group (age ≤25 years). The most commonly received vaccine was Pfizer (67.3%) while the most common side effect was local pain at the site of injection (89.4%) and tiredness (76.7%). Females were significantly more being associated with having COVID-19 vaccine side effects, while complained about fever was significantly higher in the AstraZeneca vaccine (p<0.001). Conclusions: Our findings were consistent with literatures, our study finds local pain at the site of injection, tiredness, muscle pain, headache and fever as the most common side effects of the COVID-19 vaccine. The side effects of the COVID-19 vaccine had a greater impact on female respondents than their male counterparts.